Education and citizenship in Alexis de Tocqueville - Usategui Basozabal, Elisa (Historia y Memoria de la Educación, 2023)
Education, to Alexis de Tocqueville, constitutes a fundamental tool for counteracting the inherent risks of individualism in democratic societies. Given the loss of social connections, the objective of education is to forge strong civic identities and to encourage active participation in the social fabric. Tocqueville considers essential for the maintenance of liberal democracy an education for freedom that cultivates the intellectual and moral capacities of men and women alike. At the same time, being a staunch advocate of a harsh sexual division of labor, he would have women locked within the narrow confines of the home. At the same time, Tocqueville’s approach to education enables a perspective that goes beyond neoliberal interpretations of his thinking. On the one hand, equality does not appear as a threat to freedom, but, on the contrary, it helps to construct fair political and social organization that allows the free development of individuals while facilitating social solidarity and fostering material and intellectual progress. At the same time, the state plays a major role through its responsibility for defining and implementing an educational policy that contributes to forming a populace that is freer, more critical and less subject to inequalities. Therefore, Tocqueville is not a standard liberal. He considers it necessary for the state to intervene in the educational, social and economic fields. The state must ensure solidarity with a view towards general interest and, at the same time, foster the protagonism of civil society. And all this, in and from a position of freedom.